Structural features of carnivorous plant (Genlisea, utricularia) tubers as abiotic stress resistance organs - Płachno, Bartosz J.; Silva, Saura R. [UNESP]; Świątek, Piotr; Dixon, Kingsley W.; Lustofin, Krzystof; Seber, Guilherme C. [UNESP]; Miranda, Vitor F. O. [UNESP] (MDPI, 2020)
Carnivorous plants from the Lentibulariaceae form a variety of standard and novel vegetative organs and survive unfavorable environmental conditions. Within Genlisea, only G. tuberosa, from the Brazilian Cerrado, formed tubers, while Utricularia menziesii is the only member of the genus to form seasonally dormant tubers. We aimed to examine and compare the tuber structure of two taxonomically and phylogenetically divergent terrestrial carnivorous plants: Genlisea tuberosa and Utricularia menziesii. Additionally, we analyzed tubers of U. mannii. We constructed phylogenetic trees using chloroplast genes matK/trnK and rbcL and used studied characters for ancestral state reconstruction. All examined species contained mainly starch as histologically observable reserves. The ancestral state reconstruction showed that specialized organs such as turions evolved once and tubers at least 12 times from stolons in Lentibulariaceae. Different from other clades, tubers probably evolved from thick stolons for sect. Orchidioides and both structures are primarily water storage structures. In contrast to species from section Orchidioides, G. tuberosa, U. menziesii and U. mannii form starchy tubers. In G. tuberosa and U. menziesii, underground tubers provide a perennating bud bank that protects the species in their fire-prone and seasonally desiccating environments.
Keywords: Abiotic stress; Brazilian Cerrado; Bud-bearing structures; Campo rupestre; Carnivorous plants; Kwongan; Lentibulariaceae; Plant anatomy; Starch grains; Tubers